Utilization of Tofu Wastewater for Environmental Conservation and Economic Improvement in Taman Village, Grujungan District, Bondowoso Regency - Sefia, Dian Putri; Suprianik, Suprianik (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The processing of tofu wastewater into organic liquid fertilizer in Taman Village, Grujungan District, Bondowoso Regency, was conducted to utilize wastewater that often causes environmental issues. This study aims to evaluate the potential of tofu wastewater in producing organic liquid fertilizer using a Community-Based Research (CBR) approach. A descriptive qualitative research method was employed, including observation, interviews, documentation study, and literature review. Observations revealed that tofu wastewater is yellowish-brown, has an acidic odor, and contains organic materials such as proteins, carbohydrates, and fats. The production process of organic liquid fertilizer involves collecting wastewater, fermenting with EM4 and molasses, filtering, and packaging. The fermentation results in a liquid fertilizer that can improve soil fertility and reduce environmental pollution. The program also has the potential to increase community awareness of waste management and provide economic benefits through enhanced agricultural productivity. Thus, this study shows that tofu wastewater has significant potential as a raw material for effective organic liquid fertilizer, offering notable environmental and social benefits.